Structured Flexibility in Ummi Method Quality Assurance: Balancing Control and Contextual Adaptation Across Islamic Educational Institutions - Imam Azhar; Zainul Fuad (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
This study examines the implementation of quality assurance mechanisms in Qur'anic learning through the UMMI Method across diverse Islamic educational institutions; investigating patterns of fidelity, adaptation, and the tensions between standardization and contextual flexibility. A mixed-method design was employed with a sample of 50 institutions. Quantitative data comprised supervision assessments across ten quality assurance domains, while qualitative data from 347 pages of supervisory notes underwent systematic six-stage coding. Correlation analysis demonstrated strong relationships between quality control systems and student reading quality (r = 0.669, p < 0.001), and between student grouping systems and coordinator qualifications (r = 0.653, p < 0.001). However, institutional commitment showed non-significant correlations with most implementation variables. Qualitative findings revealed four quality assurance mechanisms teacher certification, standardized learning materials, seven-step methodology, and centralized quality control alongside three implementation tensions: resource constraints, cultural integration challenges, and standardization-contextualization tensions. This study introduces structured flexibility a quality assurance model that balances methodological fidelity with contextual adaptation. This independent, large-scale mixed-methods study provides empirical evidence on how quality assurance operates in religious education, contributing to the emerging literature on the quality of Islamic education and offering a framework applicable to diverse religious educational contexts